Tolerância a secagem de sementes de cacau: Enzima Superóxido Dismutase como marcador bioquímico - Tronco, Isadora de Andrade (Universidade Federal de São Carlos, 2025)
Cocoa is a recalcitrant species, as its seeds do not suffer natural desiccation after physiological maturity and are dispersed with high water contents in the environment. One of the difficulties in conserving recalcitrant species is their lower tolerance to low temperatures and low water content, as they do not survive long periods of storage. This sensitivity during storage is related to the inefficient response of defense mechanisms to stress conditions. These mechanisms, such as antioxidant enzymes, such as superoxide dismutase (SOD), are responsible for removing the free radicals that cause cell death. The aim of this study was to determine the activity of the enzyme superoxide dismutase (SOD) as a biochemical marker of drying sensitivity in recalcitrant cocoa seeds (Theobroma cacao L). For this, two batches of cocoa seeds, extracted from mature fruit, were subjected to continuous drying in a forced-air oven at 36 ± 2°C to obtain treatments with different water contents. Drying times were: 0 h, 3 h, 6 h, 9 h, 12 h, 15 h, 18 h, 21 h, 24 h, 27 h, 30 h. The seeds from each treatment were evaluated for water content and physiological potential using the germination test and the tetrazolium test. In addition, the seeds from all the treatments in both batches were subjected to biochemical analysis to assess the activity of the SOD enzyme. There was a reduction in viability as assessed by the germination and tetrazolium tests in both batches as they dried. The critical water content of the seeds was reached at 43.61% water content (batch 1) and 66.04% water content (batch 2). The activity of SOD was different between the batches, however, in batch 2, the decrease in SOD occurred after the seeds reached the critical water content. Therefore, this enzyme can be used as a marker of sensitivity to desiccation for quality lots.
Drying tolerance of cocoa seeds: Superoxide Dismutase enzyme as a biochemical marker
Keywords: Theobroma cacao L; Sementes recalcitrantes; Qualidade de sementes; Recalcitrant seeds; Seed Quality; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA